(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
Image improvement and edge discovery are very important in the digital globe to discover the knowledge relating to an entity similar to strength, level, contrast, range, limitations, missing and hidden areas or boundaries etc. There are very a small amount of methods and algorithms to show the finer facts of an aim. The primary we planned edge detection method explores the hidden boundaries in a extremely easy approach. Our other future technique of enhancement finds its path to depiction and enhances the darkest observation of an aim .